Human rights at risk : global governance, American power, and the future of dignity - Regilme, Salvador Santino F., Jr; Hadiprayitno, Irene; Storey, Alice; Eccleston-Turner, Mark; Jordaan, Eduard; Raharja, Dinna Prapto; Yip, Ka Lok; Ba, Oumar; Simangan, Dahlia; Davis, Jeffrey (Rutgers University Press, 2022)
Human Rights at Risk brings together social scientists, legal scholars, and humanities scholars to analyze the policy challenges of human rights protection in the twenty-first century. The volume is organized based on three overarching themes that highlight the challenges and risks in international human rights: international institutions and global governance of human rights; thematic blind spots in human rights protection; and the human rights challenges of the United States as a global and domestic actor amidst the contemporary global shifts to authoritarianism and illiberal populism. One of the very few books that offer new perspectives that envision the future of transnational human rights norms and human dignity from a multidisciplinary perspective, Human Rights at Risk comprehensively examines the causes and consequences of the challenges faced by international human rights. Scholars, students, and policy practitioners who are interested in the challenges and reform prospects of the international human rights regime, United States foreign policy, and international institutions will find this multidisciplinary volume an invaluable guide to the state of global politics in the twenty-first century.